100 000 years of beauty - Azoulay, Élisabeth; Vigarello, Georges; Nouschi, Marc; Gaillard, Françoise (Ěditions Babylone, 2009)
A collection of works that focus on concepts of beauty and on customs of different civilisations across human history. Intended for professional and general public.
Keywords: History; Clothing; humanitní vědy a umění; estetická medicína; Self Care; Skin Care; dějiny; kosmetické techniky; Beauty; odívání; psychologie, klinická psychologie; krása; péče o kůži; Culture; Cosmetic Techniques; kultura; péče o sebe